Migration, risk and livelihoods: A Chinese case - Heather Xiaoquan Zhang (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2010)
China has turned from a 'low risk' to a 'high risk' society since the start of the market reforms in the late 1970s. Market, while bringing diverse livelihood opportunities to rural people, has simultaneously distributed risks, and the exposure and vulnerability to them unequally among different social groups. This paper attempts to apply the risk concept to the study of one of the most socially disadvantaged groups in China, namely rural-urban migrants, through analysing the narratives of members of a migratory family of the Hui Muslim national minority from the Qinghai-Tibet Plateau, who run a business in the northern city of Tianjin. Drawing on ethnographic fieldwork, the research adopts an actor-oriented perspective combined with qualitative longitudinal research methodology (or 'extended case method') to delineate a livelihood trajectory of this family, and explore the relationships between livelihood, risk, social networks, agency and public policy interventions.
Keywords: 330; rural-urban migration; risk; contingency; uncertainty; livelihood; social networks; agency; social security; translocality; longitudinal research; narrative; extended case method; China